Prognostic value of admission NHHR for functional recovery in acute ischemic stroke - Kong, Xiangqi; Yuan, Xinyue; Wang, Haobo; Zhao, Mina; Jing, Wei (Frontiers in Endocrinology, 2026)
BackgroundEarly risk stratification in acute ischemic stroke (AIS) is critical for guiding management and improving outcomes. The ratio of non–high-density lipoprotein to high-density lipoprotein cholesterol (NHHR) represents the equilibrium between pro-atherogenic and anti-atherogenic lipoproteins, potentially capturing both lipid metabolism and inflammatory status, but its prognostic value in AIS remains unclear.MethodsWe retrospectively analyzed 812 first-ever AIS patients. Admission NHHR was calculated from routine lipid panels. The study’s main outcome was 90-day functional status, determined using the modified Rankin Scale. Associations with NHHR were examined through multivariable logistic regression, quartile analyses, restricted cubic spline (RCS) modeling, and subgroup analyses.ResultsAmong 812 patients, 255 (31.4%) had unfavorable outcomes. Elevated NHHR showed an independent correlation with unfavorable 90-day functional outcomes (adjusted OR per unit increase, 1.233; 95% CI, 1.058–1.439; P = 0.0076). RCS analysis demonstrated a gradual rise in risk with increasing NHHR (P for trend = 0.043; P for nonlinearity = 0.584). Subgroup analyses showed consistent associations across sex, stroke severity, smoking, drinking, hypertension, and diabetes.ConclusionAdmission NHHR is a simple, inexpensive, and robust predictor of 90-day unfavorable outcomes in AIS. It provides a novel integrated lipid–inflammation marker for early risk stratification, warranting further validation in prospective studies.